LOTUS BIRTH ATAU KELAHIRAN TERATAI PADA IBU DALAM PERSALINAN: (LITERATURE REVIEW) - astri yuliandini; Emmi Wahyuni (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2022)
Lotus birth is the practice of leaving the umbilical cord unbroken until the separation occurs naturally. Our case series reports describe labor characteristics, neonatal clinical course, umbilical cord and placenta management, maternal reasons for lotus birth, and desire for future lotus births (Monroe et al., 2019). Kaeda lotus birth is believed to have started in the United States and even believed to have been practiced in Balinese and Aboriginal culture in Australia. In addition, he is also associated with practices that have been carried out in Hinduism as narrated in the story of the birth of Vishnu. This method of birth also exists in religious teachings such as Buddhism, Hinduism, Christianity and Judaism. (Mohamed, Abdullah and Ab. Rahman, 2018). The purpose of this literature review is to find out lotus birth or lotus birth in mothers in labor. The method used in this paper is a Literature Review study and the source search used is Pubmed, Science Direct, Google Scholar, and Mandeley. Literature search using the keywords "lotus birth in labor, lotus birth and lotus birth or lotus birth in labor". Conclusion: lotus birth can provide benefits to newborns by keeping the placenta clean and free of bacteria so as not to cause infection